2011
DOI: 10.5455/vetworld.4.332
|View full text |Cite
|
Sign up to set email alerts
|

Protozoan Diseases of Livestock in Arunachal Pradesh - An Overview

Abstract: The people (Tribes) of Arunachal Pradesh have the natural tendency to remain close contact with animals since immortal. The domestic animals are kept in basement of the house with human occupants in the first floor of same house. They remain in close contact with cattle, sheep, goat, pigs, poultry, cats and dogs throughout the year, exposing them to many animal born diseases of occupational risk. People are not aware of zoonotic diseases sharing between domesticated animal and human beings except for Rabies. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…However, confirmation of the diagnosis depends on microscopic examination of Giemsa-stained thin blood smears [8,9]. The demonstration of Koch’s blue bodies in the lymphocytes and monocytes of the lymph node smear or peripheral blood film is pathognomonic of the disease [10]. …”
Section: Introductionmentioning
confidence: 99%
“…However, confirmation of the diagnosis depends on microscopic examination of Giemsa-stained thin blood smears [8,9]. The demonstration of Koch’s blue bodies in the lymphocytes and monocytes of the lymph node smear or peripheral blood film is pathognomonic of the disease [10]. …”
Section: Introductionmentioning
confidence: 99%
“…Arunachal Pradesh, a North Eastern state of India, is a tribal state where there is no any taboo attached to the farming of pigs. Almost all rural household has minimum of one to two or more pigs in their backyard [12]. Pig meat (pork) is very popular among all the tribes of the state.…”
Section: Introductionmentioning
confidence: 99%
“…Reports from India, based on the results of blood smear examination, indicated that theileriosis was prevalent amongst small ruminants in different states including Karnataka, Kerala, Arunachal Pradesh, Tamil Nadu, Madhya Pradesh and Tripura (Harish et al 2006;Anumol et al 2011;Tayo et al 2011;Velusamy et al 2015;Sahu et al 2016;Das, 2017). However, there were no reports on molecular characterization of Theileria species involved in causation of this disease in sheep from Maharashtra State of India.…”
Section: Investigations On First Confirmed Outbreak Of Ovine Theilerimentioning
confidence: 99%
“…The theileriosis in small ruminants has been reported by smear examination in different states including Karnataka (Harish et al 2006), Kerala (Anumol et al 2011), Arunachal Pradesh (Tayo et al 2011), Tamil Nadu (Velusamy et al 2015), Madhya Pradesh (Sahu et al 2016) and Tripura (Das, 2017). However, studies on molecular characterization are Investigations on First Confirmed Outbreak of Ovine Theileriosis (Theileria luwenshuni) from Maharashtra State, India lacking.…”
Section: Introductionmentioning
confidence: 99%